THE IMPORTANCE OF LOGOPEDIC MASSAGE IN THE ELIMINATION OF DYSTRIA SPEECH DEFICIENCY - Erkinjonova , Ma’buda Nomozboy kizi (Educational Research in Universal Sciences, 2023)
The subject of "The importance of logopedic massage in the elimination of dystria speech deficiency" is covered in this article. The function of the language and speech organs as well as the communication between speech are both strengthened by logopedic massage. For parents and professionals, the systematic and persistent nature of massage calls for tolerance, inspiration, and project planning. Students and the community benefit from speech therapy massage as they work to overcome weaknesses.